Successes and development horizons of the department of physical education and sports and mass work at the herzen state pedagogical university of Russia - Zyukin A.V.; Fokin A.M.; Nikitina E.S.; Malysheva E.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to provide methodological justification for the socio-didactic impulses for the development of physical education at Herzen University. Methods and structure of the study. Archives on the history of physical education at the university, data from historical and archival documents, abstracts of analytical reports by university staff from different years, and recollections of contemporaries of historical events at the Department of Physical Education and in the sporting life of the Herzen State Pedagogical University of Russia were studied, and a retrospective analysis of periodicals was conducted. Results and conclusions. The dynamic nature of the physical education system at Herzen University highlights the diversity of its functions in training future school education specialists. The contradictions arising in the current model of physical education are drivers for the development of the department and the growth of its role in training well-rounded specialist teachers.